UPAYA PENINGKATKAN MODEL-MODEL PEMBELAJARAN ACTIVE LEARNING PADA GURU GEOGRAFI MELALUI WORKSHOP DI SMAN 1 PASAMAN - Hawariyun Hawariyun (JURNAL MANAJEMEN PENDIDIKAN, 2017)
Based on the observations that have been researchers did a teacher at SMAN 1 Pasaman, it was found that the ability of teachers to implement learning models are still low. The purpose of this study is to describe and obtain information about models of learning in applied by teachers. This research is a school action. The procedure in this research include planning, action, observation and reflection.The study consisted of two cycles of the four meetings. Subjects consisted of 5 teachers of Geography SMAN 1 Pasaman. Data were collected by using observation sheet. Data were analyzed using percentages. The results showed that the workshop was to improve the ability of teachers in using the models of learning in SMAN 1 Pasaman. This is evidenced by the Workshop can improve geography teachers in using the models of learning in SMAN 1 Pasaman from the first cycle to the second cycle. The average teacher's ability to apply learning models in the first cycle is 58.5 with less category, the second cycle is 86.17 Good.